Pituitary gland volume in patients with schizophrenia, subjects at ultra high-risk of developing psychosis and healthy controls: A systematic review and meta-analysis - Nordholm, Dorte; Krogh, Jesper; Mondelli, Valeria; Dazzan, Paola; Pariante, Carmine; Nordentoft, Merete (Psychoneuroendocrinology, 2013)
A larger pituitary size is thought to reflect a greater activation of the hypothalamic–pituitary–adrenal (HPA) axis, which may be related to an increase in the number and size of corticotroph cells. Some studies, but not all, indicate that pituitary volume increases before or at the onset of psychosis. There is a need for at critical appraisal of the literature on this topic accompanied by a meta-analytical evaluation of the data. We included studies comparing the volume of the pituitary gland in healthy controls and patients with schizophrenia, first episode of psychosis (FEP), schizotypal disorder or ultra high-risk (UHR) subjects. We defined three groups of subjects for the analyses: healthy controls; UHR and schizotypal patients; and patients diagnosed with first episode of psychosis, schizophrenia or schizoaffective disorder. Ten studies were included in the meta-analysis. We found a trend of a larger pituitary volume in both UHR subject who had transition to psychosis (p=0.05) and in FEP subjects (p=0.09) compared to healthy controls. There was no difference in pituitary volume between patients with schizophrenia combined with FEP versus healthy controls (p=0.52) or between UHR (with and without transition) and healthy controls (p=0.24). In a regression analysis, we demonstrated that the number of subjects receiving antipsychotics and pituitary volume were positively correlated. As previously reported in other samples, gender also had an impact on pituitary volume with females presenting with a larger mean volume. Results from this meta-analysis suggest that the pituitary gland could be increasing before the onset of psychosis. Both gender and use of antipsychotics have a major impact on the pituitary volume.